Effect of teacher and peer written corrective feedback on writing components in EFL classrooms - Elfiyanto, Sonny; Fukazawa, Seiji (JEES (Journal of English Educators Society), 2020)
This study aimed to investigate the impact of teacher and peer written corrective feedback (WCF) on Indonesian senior high school students’ writing performance. A total of 71 Indonesian senior high school students from Grade X participated in this study; 36 were provided teacher WCF and 35 peers WCF. To collect and data, the participants were asked to write a legend essay. Using qualitative data analysis, we aimed to reveal the effectiveness of teacher and peer WCF in improving students’ writing performance. Adapted scoring rubric was employed to measure students’ overall writing performance, and competencies in relation to writing components such as content, organization, grammar, vocabulary, and mechanics. The results revealed that peer WCF can better enhance students’ writing abilities compared to teacher WCF. Furthermore, students who received teacher WCF showed substantial improvement in performance relating to all writing components except mechanics. In contrast, peer WCF enhanced students’ organization and vocabulary related performance. HIGHLIGHTS: Peer WCF is more effective than teacher WCF in enhancing Indonesian senior high school students’ writing performance, especially in writing legend texts. Teacher WCF helped significantly improve four components of writing competence: content, organization, vocabulary, and language, while peer WCF positively impacted organization and vocabulary components. Combining both teacher and peer WCF could be more beneficial in improving students’ writing achievement than either type of WCF alone.